Transvestia, Vol. 18, No. 104 (1981) - Beecroft, Carol; http://id.worldcat.org/fast/506440 (Los Angeles, Calif. : Chevalier Publications, 1981)
Transvestia was published between 1960 and 1986 by Chevalier Publications in Los Angeles. It was created by Virginia Prince and edited by Prince for the first 100 issues. From the 101st issue until the final publication in 1986 (issue 111) the publication was edited by Carol Beecroft.